Effect of binaural masking noise on stuttering - a spectrographic analysis - VU, Nandur (Journal of All India Institute of Speech and Hearing)
Several reports have been made that binaural masking noise has effect on frequency of stuttering and this effect has been attributed to variations in vocal intensity, fundamental frequency of voicet rate of speech and vowel duration. Bryton and Conture (1978) have analyzed the speech of stutterers under binaural masking and rhythmic speech stimulation using spectrograph. They have attributed the decrease in stuttering under these two conditions to increase in vowel duration The present study was conducted to find out the effects of binaural masking noise on rate of speech, frequency of stuttering, vocal intensity level, fundamental frequency of voice, voice onset time and vowel duration.